Sport fans’ curiosity and impulsive buying: mediation of social media use intensity - Chen-Yueh Chen; Ya-Lun Chou; Yi-Hsiu Lin; Yen-Kuang Lin (Frontiers in Sports and Active Living)
IntroductionSports fans' curiosity and impulsive buying tendencies are important topics in sports marketing, yet the mediating role of social media use intensity in linking these variables remains underexplored. Grounded in the Stimulus-Organism-Response (S-O-R) theory, this study examines how social media use intensity mediates the relationship between sports fans' curiosity and impulsive buying behavior.MethodsThe study sampled 623 Taiwanese sports fans, including baseball and basketball enthusiasts, to investigate these relationships. Structural Equation Modeling (SEM) was employed to test the proposed hypotheses, focusing on the mediating effect of social media use intensity.ResultsThe results indicate that social media use intensity fully mediates the relationship between sports fans' curiosity and impulsive buying tendencies. This highlights the significant role of digital engagement in shaping consumer behavior among sports fans.DiscussionThese findings emphasize the importance of fostering social media engagement as a strategic tool in sports marketing. By transforming fans' curiosity into tangible purchasing behavior, this study provides valuable theoretical and practical contributions to understanding fan behavior and offers actionable recommendations for sports marketers seeking to enhance their marketing strategies in the digital era.